Propagation time of elastic surface waves on concrete specimens under uniaxial loads - Zoëga, Andreas; Shokouhi, Parisa; Wiggenhauser, Herbert (Journal of Structural Engineering, 2025)
The stress-dependency of the elastic surface-wave velocity in concrete was investigated in an experimental study carried out in BAM laboratories. The surface waves of frequencies well below the ultrasonic range were measured in these experiments. Velocities were measured at different load levels along different directions relative to the direction of the applied uniaxial load. It was observed that surface-wave velocity exhibits strong stress-dependency. Furthermore, stress-dependency of surface-wave velocity was found to be direction-dependent. Finally, the changes in surface-wave velocity also showed memory effects. In other words, the effects also depend on the maximum load in the loading history of the material. The influence of several parameters on the experimental results are investigated and reported here. The outcome of the experiments along with the details concerning the experimental setup and procedure are described in this paper.